Sensitivity Analysis of Online Game Addiction Model - Maulana, Dimas Avian (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The rapid advancement of the internet has led to some shifts in daily activities. Some conventional activity is now slowly shifted to online, including playing online games. Online games have both impacts, positive and negative. The advantage of online games is to help people communicate with other parties anywhere and anytime in the world. On the other hand, the negative impact is an addiction which leads to losing track of time and neglecting their responsibilities. This study aims to analyse online game addiction using a mathematical model. The mathematical model used is the SEAR model with four compartments, susceptible, exposed, addiction and recovery. The population of this study is limited to cases of addiction to online games on gadgets and ignores the factor of having professional players (e-sports). We obtained the basic reproduction number is , which means that online game addiction does not occurs in the population. Sensitivity analysis showed that the rate of susceptible gamer to be exposed gamer and the rate of individuals who addicted to online game are the parameter which prone to change. The numerical simulation also shown that the change in α brings an impact to the overall dynamics.